Combined use of SSRIs and NSAIDs increases the risk of gastrointestinal adverse effects - de Jong, Jeroen C F (Blackwell Science Inc, 2003)
AIMS: To investigate the relationship between the use of antidepressants with or without NSAIDs and the risk of gastrointestinal side-effects. METHODS: This was a population-based cohort study. Medication data of 180 000 patients from 16 pharmacies in The Netherlands were studied. The subjects were a group of 15 445 new users of antidepressants with or without NSAIDs. A review of patient profiles for cases of gastrointestinal adverse effects caused by first time use of antidepressants with or without NSAIDs was carried out. The number of first prescriptions for peptic ulcer drugs (Anatomical Therapeutic Chemical classification A02B) in the period from day 2 after starting antidepressants with or without NSAIDs until 10 days after the last dose was the main outcome measure. RESULTS: In the reference group of 619 new users of nonselective antidepressants (TCAs), the incidence of first prescriptions for peptic ulcer drugs was 0.051 (95% confidence interval 0.021, 0.105). The use of SSRIs (n = 1181) caused a slightly higher incidence rate ratio (IRR) of 1.2 (0.5, 2.8). The combined use of SSRIs and NSAIDs (n = 86) increased the IRR to 12.4 (3.2, 48.0). In contrast, the combination of nonselective antidepressants and NSAIDs (n = 74) increased the IRR to 2.5 (0.3, 20.3). CONCLUSIONS: SSRIs increase the risk of gastrointestinal adverse effects in first time users as compared with nonselective antidepressants. The combined use of SSRIs and NSAIDs strongly increases the risk of gastrointestinal adverse effects and should be avoided. The combination of nonselective antidepressants and NSAIDs does not have this effect.